Paper - Castner, C. (1703)
Proposal made to the King of Portugal for voyages in the direction of Macao, dated 17 February 1703, signed by Father Francisco Noel and C. Castner.
Manuscript reference: NLA MS 4438.
Photographs.
Original held by Ajuda Library, Portugal.
Braga Collection.
Keywords: Portugal -- Commerce -- China -- Macau (Special Administrative Region)